Senkiföldje hadirokkantak és háborús önkéntesek Jugoszláviában - Newman John Paul (Aetas, 2018)
Yugoslavia inherited a divided wartime legacy: its war veterans that had fought or served with the Allies during the war and those that had fought or served with the Central Powers. But between the two contingents of South Slav war veterans – those that had fought in the Serbian army and those that had fought for Austria-Hungary - there was a kind of middle ground, a ‘no man’s land’ occupied by veterans who did not exactly fit into either side. The most prominent groups in this middle ground were disabled veterans, South Slavs from either the Austro-Hungarian army or the Serbian army who had been permanently injured or disfigured during the war years, and the volunteers, South Slavs of all nationality and background who had opted to fight in the Serbian army’s volunteer divisions during the wars. This article explores the experiences of veterans residing in the ‘no man’s land’ in Yugoslavia.